Critical current degradation and delamination crack observation of epoxy-coated REBCO superconducting tapes after thermal cycles in liquid nitrogen. Issue 21 (1st November 2021) - Yang, Zhirong; Song, Peng; Guan, Mingzhi; Feng, Feng; Qu, Timing
Abstract: The delamination and critical current ( I c ) degradation caused by thermal stress after epoxy impregnation are threats for the application of REBa2 Cu3 O7- x (REBCO, RE = Rare earth) superconducting magnets. In this work, two types of REBCO tapes were coated by Stycast 2850FT with controlled coating geometries. Critical currents of coated samples after thermal cycles in liquid nitrogen were measured. I c degradation was found in coated samples with a free no-coating edge, when the surface coating layer was thicker than 1000 μm. It was also found that additional edge coating can help to suppress the I c degradation. Samples with degraded I c after thermal cycles showed an obvious delamination phenomenon. The morphology and location of delamination cracks were carefully observed by using focused Ion beam, scanning electron microscope, and transmission electron microscope. Delamination cracks propagated within the REBCO layer and stopped at reaching the Silver/REBCO interface. Simulations by finite element method suggest that delamination cracks are generated by the stress accumulation within the REBCO layer, which could be reduced by a full epoxy coating on both tape surface and edges. Graphical abstract: Image 1